Prevalence of asymptomatic Leishmania donovani infection and associated factors in Ethiopia: a systematic review and meta-analysis - Habtamu Belay; Adugna Abera; Esayas Aklilu; Tesfahun Bishaw; Ayinalem Alemu; Geremew Tasew; Berhanu Erko (BMC Infectious Diseases)
Abstract Background Visceral leishmaniasis is endemic in Ethiopia and caused by Leishmania donovani. Although the disease manifests with significant clinical variability, a substantial number of individuals are asymptomatic. These individuals can serve as reservoirs, complicating control efforts. However, comprehensive data on asymptomatic L. donovani infections in Ethiopia are lacking, highlighting the need for a systematic review and meta-analysis to consolidate evidence and understand the distribution and determinants of this infection. Methods PRISMA guidelines followed and registered with PROSPERO (CRD42024531454). Systematically searched electronic databases and grey literature sources up to April 13, 2024. Original research articles in English considered. Statistical analyses performed using STATA version 16. Publication bias evaluated using funnel plots and Egger’s regression tests. Pooled estimate of asymptomatic L. donovani infection derived using a random effects model. Study heterogeneity assessed using Chi-square (χ²)-based Q test (p < 0.1) and I² subgroup analysis and meta-regression conducted with significance set at p < 0.05. Result A total of 1,288 articles were identified, with 11 studies met inclusion criteria. These studies, published between 2012 and 2024, reported data from 17 districts across six regions. Sample sizes ranged from 185 to 1,682, with a total of 7,288. Six types of laboratory testing methods were employed. Prevalence of asymptomatic L. donovani infection per individual study ranged from 0.9 to 15.8%, while district-level prevalence varied from 0 to 31.1%. The overall pooled estimate of asymptomatic L. donovani infection in Ethiopia was 9.0% (95% CI: 6.0-11.0%). The pooled estimate in the Amhara region was 9.0% (95% CI: 8.0-11.0%), compared to 7.0% (95% CI: 3.0-12.0%) in other regions. Living in a household with domestic animals (OR: 2.54; 95% CI: 1.43–3.64) and being male (OR: 2.22; 95% CI: 1.21–3.23) were significantly associated with higher asymptomatic L. donovani infection. Conclusion A considerable number of asymptomatic L. donovani infections were reported in Ethiopia. Close contact with domestic animals and being male were identified as significant risk factors. Regular screening of people living in close contact with animals. This will minimize role of man as reservoir host of asymptomatic L. donovani infection VL and hence aid in disease control and management.